2002
DOI: 10.1017/s0022112001007431
|View full text |Cite
|
Sign up to set email alerts
|

The instability and breakdown of a near-wall low-speed streak

Abstract: The instability of the three-dimensional high-shear layer associated with a near-wall low-speed streak is investigated experimentally. A single low-speed streak, not unlike the near-wall low-speed streaks in transitional and turbulent flows, is produced in a laminar boundary layer by using a small piece of screen set normal to the wall. In order to excite symmetric and anti-symmetric modes separately, well-controlled external disturbances are introduced into the laminar low-speed streak through small hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
175
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(205 citation statements)
references
References 47 publications
28
175
2
Order By: Relevance
“…The sinuous mode is antisymmetric with respect to the base flow, with transversely oscillating perturbation streamlines. The sinuous mode was more rapidly growing, and was related to spanwise shear, whereas the varicose mode was associated with wall-normal shear (Saric 1994;Asai, Minagawa & Nishioka 2002).…”
Section: The Instability Due To Klebanoff Streaks In Bypass Transitionmentioning
confidence: 99%
“…The sinuous mode is antisymmetric with respect to the base flow, with transversely oscillating perturbation streamlines. The sinuous mode was more rapidly growing, and was related to spanwise shear, whereas the varicose mode was associated with wall-normal shear (Saric 1994;Asai, Minagawa & Nishioka 2002).…”
Section: The Instability Due To Klebanoff Streaks In Bypass Transitionmentioning
confidence: 99%
“…The same definition has been employed by Asai et al [3]. The positive and negative streaks are therefore defined as follows,…”
Section: Time-averaged Statistics Of Streaksmentioning
confidence: 99%
“…[4][5][6][7] These studies confirmed that the instability is of inflectional type and that the dominating instability appears as spanwise ͑sinuous͒ oscillations of the streaks. For zero-pressure-gradient boundary layers, the spatial response of a single low-speed streak submitted to a time-harmonic excitation of sinuous or varicose type has been more recently examined experimentally by Asai et al 8 The growth of the sinuous mode was observed to evolve into a train of quasi-streamwise vortices with vorticity of alternate sign. By contrast, the varicose mode led to the formation of hairpin structures made up of a pair of counterrotating vortices.…”
Section: Introductionmentioning
confidence: 99%